2023
DOI: 10.1101/2023.07.24.550367
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Bacterial cGAS-like enzymes produce 2′,3′-cGAMP to activate an ion channel that restricts phage replication

Uday Tak,
Peace Walth,
Aaron T. Whiteley

Abstract: The mammalian innate immune system uses cyclic GMP–AMP synthase (cGAS) to synthesize the cyclic dinucleotide 2′,3′-cGAMP during antiviral and antitumor immune responses. 2′,3′-cGAMP is a nucleotide second messenger that initiates inflammatory signaling by binding to and activating the stimulator of interferon genes (STING) receptor. Bacteria also encode cGAS/DncV-like nucleotidyltransferases (CD-NTases) that produce nucleotide second messengers to initiate antiviral (antiphage) signaling. Bacterial CD-NTases p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 68 publications
0
1
0
Order By: Relevance
“…Our study suggests that the proton channel function of STING is highly conserved. A recent study identified a bacterial cGAMP receptor as a potential cGAMP-activated Clchannel 32 . The surface charges on the cytosolic side of the pore suggest that STING might also allow for the flux of anions like Clin addition to H + .…”
Section: Discussionmentioning
confidence: 99%
“…Our study suggests that the proton channel function of STING is highly conserved. A recent study identified a bacterial cGAMP receptor as a potential cGAMP-activated Clchannel 32 . The surface charges on the cytosolic side of the pore suggest that STING might also allow for the flux of anions like Clin addition to H + .…”
Section: Discussionmentioning
confidence: 99%